Opacity Results Diesel Fuel: Bio Solar, Dexlite, Dex and Analysis Theoretical Flammability Limit - Hadi Pranoto; Wiwit Suprihatiningsih; Muhammad Idil Fadil; Supaat Zakaria (International Journal of Advanced Technology, 2020)
Each mixture of fuel and gas has a different flame speed. Gas will only burn at a suitable percentage of air and produce different exhaust gas opacity, opacity is a ratio of the rate of light absorption by smoke expressed in units of percent. This study aims to theoretically analyze the relationship between the flammability limit and the variation of fuel which has a different setana number associated with the exhaust gas opacity value of the engine performance test equipment. The machine performance test equipment used is the L300 engine. The methodology used is the testing of exhaust gas opacity using the Koeng OP-201 opacity meter and theoretically analyzed its relationship with the bio solar, dexlite and pertamina dex flame limits. The results of this study found that bio solar has an upper flame limit of 6.65%, a lowerflame limit of 0.53%, and an average opacity value of 12.1%. Dexlite has an upper limit of 6.70%, a lower limit of 0.53%, and an average opacity value of 10.5%. Pertamina dex has an upper limit of 6.68%, a lower limit of 0.53%, and an average opacity value of 9.21%.